(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study including upper gastro - intestinal endoscopic findings of 1998 patients complaining from dyspepsia, 803 (40%) of them were found to have normal endoscopic findings and 1195 (60%) found to have upper gastro - intestinal abnormalities. Duodenal ulcer represents the highest frequency (24%) of these abnormalities followed by gastritis (13%), duodenitis (7%), gastro duodenitis (4.4%), hiatus hernia & prolapse gastropathy (3.9%), reflux esophagitis (3.1%), gastric tumor (1.7%), gastric ulcer (1.3%), gastric outlet obstruction (1.2%) while tumor of esophagus found to be the lowest value (0.4%).Of the all examined cases as well as cases with abnormal endoscopy (1195 case), the highest number of referred cases were from the age group 21-30year, and the lowest was from the age group 81-90years. Also, we found that when the age is more than 60years of age, more than 79% of their endoscopic findings were abnormal.There were no significant sex differences among all studied cases except for tumor of esophagus and hiatus hernia as showed male predominance.